2022
DOI: 10.1101/2022.03.02.22271697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recurrent SARS-CoV-2 Mutations in Immunodeficient Patients

Abstract: Long-term SARS-CoV-2 infections in immunodeficient patients are an important source of variation for the virus but are understudied. Many case studies have been published which describe one or a small number of long-term infected individuals but no study has combined these sequences into a cohesive dataset. This work aims to rectify this and study the genomics of this patient group through a combination of literature searches as well as identifying new case series directly from the COG-UK dataset. The spike ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 49 publications
3
25
0
Order By: Relevance
“…This is consistent with other studies in sub-Saharan Africa where patients admitted with COVID-19 during Omicron waves had comparatively less severe disease [ 16 , 27 , 28 ]. There is a high burden of HIV and a low SARS-CoV-2 vaccine coverage in Malawi [ 29 ], this provides a plausible environment for the emergence of novel VOCs [ 30 33 ]. It is crucial to identify potential VOCs rapidly and report these internationally.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies in sub-Saharan Africa where patients admitted with COVID-19 during Omicron waves had comparatively less severe disease [ 16 , 27 , 28 ]. There is a high burden of HIV and a low SARS-CoV-2 vaccine coverage in Malawi [ 29 ], this provides a plausible environment for the emergence of novel VOCs [ 30 33 ]. It is crucial to identify potential VOCs rapidly and report these internationally.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, S/Q493R (as occurs in BA.1) escapes some class 2 neutralizing antibodies ( Liu et al 2022 ), and S/Q493R and S/Q493K escape mutations have been selected in VSV in vitro experiments ( Weisblum et al 2020 ). S/Q493K, S/G496S, S/Q498R, and S/Y505H mutations have also all arisen previously in the context of chronic SARS-CoV-2 infections ( Choi et al 2020 ; Maponga et al 2022 ; Riddell et al 2022 ; Wilkinson et al 2022 ). The S/Q498R and S/Q493R mutations yield two additional salt bridges when binding human ACE2 ( Mannar et al 2022 ; McCallum et al 2022 ) and it is likely that the increased affinity of BA.1 Spike for human ACE2 relative to that of Alpha, Beta, Delta, and Wuhan-Hu-1 ( Cameroni et al 2022 ; Meng et al 2022 ; Peacock et al 2022 ) will further decrease its sensitivity to neutralization.…”
Section: Resultsmentioning
confidence: 81%
“…Several studies have now shown evidence of recurrent SARS-CoV-2 mutations in immunocompromised patients [1517], with some suggesting the detection of a variant-like lineage which arose from a chronic infection that spilled over into a local population [43]. Another major implication of our work is that we can now quantitatively explain the possibility of such events and find the expected time that it takes for a new VOC to emerge from a within-host evolutionary pathway that involves any number of mutations.…”
Section: Discussionmentioning
confidence: 99%